Body weight and wool production responses to supplementary feeding in Menz sheep and their crosses with Awassi and corriedale - Lemma, S.; Awgichew, K.; Tiyo, D.; Fletcher, I. (1993)
Purebred Menz, first-cross Awassi x Menz, and first-cross Corriedale x Menz lambs were born and reared together under common environmental and management conditions. Before they reached six months of age, animals of each sex in each genotype were allocated to two treatment groups. Both groups grazed together on unimproved pasture during the day and at night only one group was given supplementary feed. The two treatments were maintained until yearling age. However, because ewe lambs were joined early with fertile rams and began to lamb at 12 months of age, treatment effects for ewes were assessed from body weight taken at 315 days of age to avoid confounding with increasing conceptus weight during late pregnancy. Supplementary feeding significantly increased both male and female body weights and yearling wool production in all genotypes. Mean ewe body weights at 315 days of age for unsupplemented crosses were: 15.8 kg Menz, 18.3 kg Awassi, and 17.8 kg Corriedale. The values for the supplemented crosses were: 20.7 kg Menz, 27.7 kg Awassi, and 26.2 kg Corriedale. The mean yearling weights for unsupplemented rams were: 17.5 kg Menz, 21.3 kg Awassi, and 20.5kg Corriedale. The values for the supplemented rams were: 25.8 kg Menz, 37.5 kg Awassi, and 35.0 kg Crriedale. Average yearling wool weights for unsuplemented animals of both sexes were: 0.65 kg Menz, 0.85 kg Awassi and 1.07 kg Corriedale. The wool weights for supplemented groups were: 0.75 kg Menz, 1.21 kg Awassi, and 1.36 kg corriedale. Treatment and genotype interactions were highly significant for all measurements, which shows that differences in productivity between indigenous and crossbred genotypes were greater under supplemented than unsupplemented conditions. These results illustrate the necessity of providing extra inputs for crossbred genotypes to get the full benefit of their greater production potential.